Analysis of Growth and Development of Liquid Crystals in Pharma Ceutical Applications - Patel Dipesh kumar Babubhai, Dr. Sanjay Rathore (Mathematical Statistician and Engineering Applications, 2022)
Our society’s healthcare system is in desperate need of reform. Work on the development of novel pharmaceuticals requires the collaboration of scientists from both industry and academia. Oral dose forms containing crystalline solids of the active ingredient are the chosen mode of administration for the majority of medications. Crystallization is consequently essential in medication development, as it produces crystalline active pharmacological ingredients (API). The creation of a process relies heavily on an understanding of the impact of key process parameters on the final product’s qualities. The development of crystallisation processes at the laboratory scale can currently be supported by a number of technologies. There are numerous technologies that can be employed to construct pharmaceutical crystallisation procedures. A method is presented for organising, designing, and carrying out laboratory-scale crystallisation studies in a reliable manner. This approach enables precise control of the essential crystal qualities that influence the new drug’s pharmacokinetics and bioavailability, among other things. A focus on laboratory research to aid in the creation of new pharmaceuticals is emphasised throughout the piece.